Formação de professores de física no centro de estudos superiores de Parintins/UEA - Gomes, Edilson Barroso (2012)
That research has as objective analyzes as the curriculum influence in the teachers' formation in the Course of Degree in Physics of CESP/UEA of Parintins. It was born of authors Nardi's knowledge & Camargo (2008), Delizoicov and Angotti (1994), Moreira (1986), Krasilchik (1987), regarding the curriculum and the teachers' of Physics formation in Brazil and in Amazon, fact that is now being discussed thoroughly in several works about teachers' formation, some of these works are related in the State of the Art. The methodology of the research follows Gil's recommendations (2010), Creswell (2007) for collection and analysis of the data regarding the teachers' opinions and students of Physics Course on the formation process that you/they are involved. The research is qualitative, being characterized by using the method fenomenológico. The used technique went to the interview with eight teachers that supply classes in the course Physics and their answers were related with the answers of the questionnaires developed with ninety two students of the first, third and fifth period Course of Physics. We identified that some teachers ignore the curriculum of Physics Course and they develop their activities based in the menus of the disciplines. The students, independent of the period also has difficulty in understanding what is the curriculum and their relationships with their pedagogic and professional formation in the Center of Superior Studies in Parintins. Some points of Physics curriculum need to be modified according to the local reality, as the grating curricular, effectiveness of the laboratory in Physics teaching, the teachers' methodology. And, possibly, practiced this proposal there will be improvements in these teachers' of Physics formation in this Unit.